The Effect of Leverage on Profitability with Firm Size and Sales Growth as Moderating Variables in LQ-45 Companies Listed on the Indonesia Stock Exchange - Firdaus Indrajaya Tuharea; Dini Pramitasari; Mutiara Cahyani (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study examines the effect of financial leverage (Debt to Equity Ratio) on corporate profitability, measured by Return on Assets, Return on Equity, and Net Profit Margin, among companies listed in the LQ-45 Index of the Indonesia Stock Exchange. Firm size and sales growth are analyzed as moderating variables to understand how internal capacity and market performance influence the leverage–profitability relationship. The research applies a quantitative approach using secondary data from 45 listed companies during 2022–2024. Panel data analysis with a Fixed Effect Model (FEM) and Generalized Least Squares (GLS) correction was employed to address heteroscedasticity and autocorrelation issues. The results indicate that leverage has a significant negative effect on profitability, confirming the relevance of the Trade-Off Theory in the Indonesian capital market context. Moreover, firm size strengthens this negative relationship, while sales growth moderates it positively. These findings provide new insights into how financial structure decisions affect performance among large and liquid firms in emerging markets. The study contributes to financial management literature by validating classical capital structure theories within Indonesia’s dynamic market environment.